2022
DOI: 10.3390/foods11142160
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive and Rapid Detection of Pathogenic Yersinia enterocolitica Based on the CRISPR/Cas12a Nucleic Acid Identification Platform

Abstract: Yersinia enterocolitica is a dangerous foodborne human pathogen that mainly causes gastroenteritis. Ideal methods for the detection of pathogens in food should be rapid, sensitive, specific, and cost effective. To this end, novel in vitro nucleic acid identification methods based on clustered, regularly interspaced short palindromic repeats (CRISPR)-associated protein (Cas) endonuclease have received increasing attention. In this study, a simple, visual, and ultrasensitive method, based on CRISPR/Cas12a with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For example, Tian et al (2021) compared the use of RPA-CRISPR/Cas12a and qPCR in detecting L. monocytogenes in milk and found that the sensitivity of RPA-CRISPR/Cas12a was 100 times higher than that of the qPCR method, with a detection limit of 10 CFU/mL, without requiring enrichment. Similarly, Xiao et al (2022) found that RPA-CRISPR/Cas12a outperformed the qPCR method in detecting Y. enterocolitica in pork, as it was able to detect this pathogen at a concentration of 1 cfu/mL, whereas qPCR could only detect it at a concentration of 10 2 cfu/mL. In a separate study, Liu et al (2022a) compared the specificity and sensitivity of RPA-CRISPR/Cas12a and qPCR in detecting Salmonella spp.…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tian et al (2021) compared the use of RPA-CRISPR/Cas12a and qPCR in detecting L. monocytogenes in milk and found that the sensitivity of RPA-CRISPR/Cas12a was 100 times higher than that of the qPCR method, with a detection limit of 10 CFU/mL, without requiring enrichment. Similarly, Xiao et al (2022) found that RPA-CRISPR/Cas12a outperformed the qPCR method in detecting Y. enterocolitica in pork, as it was able to detect this pathogen at a concentration of 1 cfu/mL, whereas qPCR could only detect it at a concentration of 10 2 cfu/mL. In a separate study, Liu et al (2022a) compared the specificity and sensitivity of RPA-CRISPR/Cas12a and qPCR in detecting Salmonella spp.…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
“…A combination of RPA arrays with CRISPR/Cas12a (RPA-CRISPR/Cas12a) can perform better than or at least comparable to the qPCR method in detecting pathogens in food samples ( Liu et al, 2022a , Tian et al, 2021 , Xiao et al, 2022 ). For example, Tian et al (2021) compared the use of RPA-CRISPR/Cas12a and qPCR in detecting L. monocytogenes in milk and found that the sensitivity of RPA-CRISPR/Cas12a was 100 times higher than that of the qPCR method, with a detection limit of 10 CFU/mL, without requiring enrichment.…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
“…Additionally, the RPA-CRISPR/Cas12a strategy has been used for the detection of other foodborne pathogenic bacteria ( Listeria monocytogenes , Yersinia enterocolitica , Staphylococcus aureus , Campylobacter jejuni , Escherichia coli , etc.) in food production animals at attomolar level [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Current Applications Of Crispr/cas-based Nucleic Acid Detect...mentioning
confidence: 99%